Philosophical attitude, childhood, and teacher education - Mariño Díaz, Liliana Andrea; Pulido Cortés, Oscar; Morales Mora, Lola María (Universidad Pedagógica y Tecnológica de Colombia, 2016)
This paper discusses the research results on philosophical attitude and infancy: education and transformation of teachers; being its goal to design a proposal for the development of a philosophical attitude. These reflections arose from a research experience at the kindergarten of the Pedagogical and Technological University of Colombia, using the qualitative paradigm with a critical-social approach. This paradigm builds on the relationship between the philosophical attitude and childhood. The first is understood as a disposition and lifestyle reflected in critical, creative and sensitive thinking; while the second one is appreciated as attitude and not as a chronological and unfinished stage. A teacher training proposal was developed, supported by three tools: writing, reading, and problem solving; elements addressed based on the philosophy program for children. This proposal produced education and transformation practices, in terms of continuous learning, self-reflexion,criticism, creation, questioning and searching; leading to the care of self, of others, and of what is alien, as a condition to embody the teacher’s role in the creation of spaces that strengthen the philosophical attitude.